2021
DOI: 10.2147/ijn.s299696
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing Activity of Opuntia ficus-indica Fixed Oil Formulated in a Self-Nanoemulsifying Formulation

Abstract: Introduction: Delayed wound healing represents a common health hazard. Traditional herbal products have been often utilized to promote wound contraction. The current study aimed at assessing the wound healing activity of Opuntia ficus-indica seed oil (OFI) and its self-nanoemulsifying drug delivery system (OFI-SNEDDS) formula in a rat model of fullthickness skin excision. Methods: Based on droplet size, an optimized OFI-SNEDDS formula was prepared and used for subsequent evaluation. Wound healing activity of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…On the dorsal interscapular region of each rat, a 225 mm 2 (1.5 cm × 1.5 cm) full-thickness cutaneous square wound was made by removing a skin patch, and wounds were kept undressed until the end of the experiment ( Davoodi-Roodbordeii et al, 2019 ). Lidocaine hydrochloride (2%) containing 1: 80,000 epinephrine (4.4 mg/kg) was S.C injected into rats to reduce pain near the wound area immediately after wounding ( Koshak et al, 2021 ). To maintain aseptic conditions, bench surfaces and cages to be used were cleaned by wiping over with a wet cloth that had been soaked with a cleaning agent, followed by disinfection with 70% alcohol.…”
Section: Methodsmentioning
confidence: 99%
“…On the dorsal interscapular region of each rat, a 225 mm 2 (1.5 cm × 1.5 cm) full-thickness cutaneous square wound was made by removing a skin patch, and wounds were kept undressed until the end of the experiment ( Davoodi-Roodbordeii et al, 2019 ). Lidocaine hydrochloride (2%) containing 1: 80,000 epinephrine (4.4 mg/kg) was S.C injected into rats to reduce pain near the wound area immediately after wounding ( Koshak et al, 2021 ). To maintain aseptic conditions, bench surfaces and cages to be used were cleaned by wiping over with a wet cloth that had been soaked with a cleaning agent, followed by disinfection with 70% alcohol.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that self-emulsifying drug delivery systems offer a significant interfacial area for the partitioning of the medication between oil and water is another benefit they have over straightforward oily solutions. Therefore, these systems may provide an improvement in the pace and amount of absorption as well as more consistent plasma concentration profiles for lipophilic medicines with dissolution-limited oral absorption [ 126 ].…”
Section: Localised Delivery Systems For Wound Healingmentioning
confidence: 99%
“…Both the seed oil and its self‐nanoemulsifying formulation significantly enhanced hydroxyproline content in skin, upregulated Col1A1 mRNA expression, and enhanced transforming factor‐beta (TGF‐β) expression, while they significantly decreased tumor necrosis factor‐α (TNF‐α) and interleukin 6 (IL‐6) in wound tissues. The self‐nanoemulsifying formulation enhanced vascular endothelial growth factor (VEGF) expression, so it improved angiogenesis, and it also significantly enhanced SOD, GSH, and GPx wound tissue content (Koshak et al, 2021). Khémiri et al (2019) also reported in‐vivo cutaneous wound healing effects of the seed oil on a full‐thickness injury using an excisional wound healing model in rats through reducing the re‐epithelialization phase, enhancing the speed of wound contraction, and improving the external scar's aspect.…”
Section: Biological Activitiesmentioning
confidence: 99%